Toleransi, pluralisme, dan multikulturalisme: Tiga pilar kohesi sosial dalam masyarakat indonesia yang majemuk - salsabilah, safira (Maliki Interdisciplinary Journal, 2026)
Indonesia is a pluralistic nation with a high degree of ethnic, religious, racial, and cultural diversity. This diversity is both a wealth and a challenge in maintaining national unity. This article examines the role of tolerance, pluralism, and multiculturalism as key pillars in building social cohesion in Indonesia. Tolerance serves as the foundation for accepting differences; pluralism acts as a value that transforms attitudes of "allowing" into "respecting"; while multiculturalism exists as a policy dimension that ensures diversity is realized in institutional structures and public policies. These three pillars do not stand alone but organically support each other in forming sustainable social cohesion. Through an integrative analytical approach, this article shows that the synergy of these three is a real prerequisite for creating harmony amidst diversity. The implementation of these values ​​requires cooperation between the government, educational institutions, and society through inclusive policies, early character education, and ongoing interfaith and cultural dialogue. By strengthening the synergy of tolerance, pluralism, and multiculturalism, Indonesia can make its diversity a key strength in building a united, just, and harmonious nation.